Animal Models for the Study of Hepatitis B Virus Pathobiology and Immunity: Past, Present, and Future - Zhang, Xiaonan; Wang, Xiaomeng; Wu, Min; Ghildyal, Reena; Yuan, Zhenghong (Frontiers in Microbiology, 2021)
Hepatitis B virus (HBV) infection is a global public health problem that plagues approximately 240 million people. Chronic hepatitis B (CHB) often leads to liver inflammation and aberrant repair which results in diseases ranging from liver fibrosis, cirrhosis, to hepatocellular carcinoma. Despite its narrow species tropism, researchers have established various in vivo models for HBV or its related viruses which have provided a wealth of knowledge on viral lifecycle, pathogenesis, and immunity. Here we briefly revisit over five decades of endeavor in animal model development for HBV and summarize their advantages and limitations. We also suggest directions for further improvements that are crucial for elucidation of the viral immune-evasion strategies and for development of novel therapeutics for a functional cure.